What–where–when memory and encoding strategies in healthy aging - Cheke, Lucy G. (Learn Mem, 2016)
Older adults exhibit disproportionate impairments in memory for item-associations. These impairments may stem from an inability to self-initiate deep encoding strategies. The present study investigates this using the “treasure-hunt task”; a what–where–when style episodic memory test that requires individuals to “hide” items around complex scenes. This task separately assesses memory for item, location, and temporal order, as well as bound what–where–when information. The results suggest that older adults are able to ameliorate integration memory deficits by using self-initiated encoding strategies when these are externally located and therefore place reduced demands on working memory and attentional resources.